High Blood Pressure Effects on the Blood to Cerebrospinal Fluid Barrier and Cerebrospinal Fluid Protein Composition: A Two-Dimensional Electrophoresis Study in Spontaneously Hypertensive Rats - Ibrahim González-Marrero; Leandro Castañeyra-Ruiz; Juan M. González-Toledo; Agustín Castañeyra-Ruiz; Hector de Paz-Carmona; Rafael Castro; Juan R. Hernandez-Fernaud; Agustín Castañeyra-Perdomo; Emilia M. Carmona-Calero (International Journal of Hypertension)
The aim of the present work is to analyze the cerebrospinal fluid proteomic profile, trying to find possible biomarkers of the effects of hypertension of the blood to CSF barrier disruption in the brain and their participation in the cholesterol and β-amyloid metabolism and inflammatory processes. Cerebrospinal fluid (CSF) is a system linked to the brain and its composition can be altered not only by encephalic disorder, but also by systemic diseases such as arterial hypertension, which produces alterations in the choroid plexus and cerebrospinal fluid protein composition. 2D gel electrophoresis in cerebrospinal fluid extracted from the cistern magna before sacrifice of hypertensive and control rats was performed. The results showed different proteomic profiles between SHR and WKY, that α-1-antitrypsin, apolipoprotein A1, albumin, immunoglobulin G, vitamin D binding protein, haptoglobin and α-1-macroglobulin were found to be up-regulated in SHR, and apolipoprotein E, transthyretin, α-2-HS-glycoprotein, transferrin, α-1β-glycoprotein, kininogen and carbonic anhidrase II were down-regulated in SHR. The conclusion made here is that hypertension in SHR produces important variations in cerebrospinal fluid proteins that could be due to a choroid plexus dysfunction and this fact supports the close connection between hypertension and blood to cerebrospinal fluid barrier disruption.